Merger Control and Enterprise Competitiveness - Empirical Analysis and Policy Recommendations - Johan Stennek; Frank Verboven (The Research Institute of Industrial Economics (IUI), 2001)
This report studies the importance of efficiency gains from horizontal mergers. A general theme throughout this report is that efficiency gains, and their pass-on to consumers, may vary substantially from merger to merger. For this reason it seems appropriate to reconsider current practice in European merger control, which does not allow the merging parties to appeal to an efficiency defence. Our report provides a detailed examination of two main parts of an efficiency analysis. The first chapter considers the presence of efficiencies from mergers, with a focus on economies of scale. The second chapter consider the pass-on of efficiencies to consumers in the form of lower prices.
Keywords: K21; L10; L40; 330; Mergers & Acquisitions; Merger Control; Competition Policy; Antitrust; Fusionskontrolle; Horizontale Integration; Skalenertrag; Wohlfahrtsanalyse; Theorie; Effizienzmarkthypothese